Dampak teknologi pada metode pembelajaran ilmu pengetahuan sosial di tingkat sekolah menengah pertama - sobih, muhammad (Maliki Interdisciplinary Journal, 2024)
This article discusses the impact of technology on Social Studies learning in Junior High School, and the associated opportunities and challenges. Technological developments have changed the way students learn and teachers teach by presenting more dynamic and engaging learning methods. However, there are still a number of barriers such as teachers’ lack of understanding of technology, infrastructure issues and financial constraints. To overcome these challenges, intensive training for teachers, improvement of school infrastructure, development of relevant learning materials, efficient fund management and active participation of parents are required. These measures are expected to increase the effectiveness of technology use in social studies learning in junior high schools, as well as provide a better quality learning experience for students.